Effect of Temperature and Microstructural Evolution of Magnesium and Aluminium Alloy Using Vacuum Diffusion Bonding - Renjith Nimal, R.J. Golden; Sivakumar, M.; Esakkimuthu, G. (International Journal of Psychosocial Rehabilitation, 2019)
This work is conducted to obtain better understanding and characterization of the diffusion bonding of similar and dissimilar metals. It also aimed to obtain optimum parameters for diffusion bonding of aluminium coating over magnesium alloy with Aluminium alloy. This work aims at developing a simple method to obtain diffusion bonding joints at relatively not low cost. On one hand, the research is intended to establish a method. This method is devised to study the physical phenomena that have significant influence on diffusion bonding such as time, temperature, pressure on joints and metallurgical characteristics. Tensile and shear tests are to be conducted. This work is conducted to obtain better understanding and characterization of the diffusion bonding of similar and dissimilar metals. It also aimed to obtain optimum parameters for diffusion bonding of aluminum coating over magnesium alloy with aluminum alloy. These two metals are jointed inside the die after finishing surface treatment. Then the die is kept inside the diffusion bonding machine by varying the time, temperature, pressure by means of load.